If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5u + 2v + -2(4u + -5v) = 0 5u + 2v + (4u * -2 + -5v * -2) = 0 5u + 2v + (-8u + 10v) = 0 Reorder the terms: 5u + -8u + 2v + 10v = 0 Combine like terms: 5u + -8u = -3u -3u + 2v + 10v = 0 Combine like terms: 2v + 10v = 12v -3u + 12v = 0 Solving -3u + 12v = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-12v' to each side of the equation. -3u + 12v + -12v = 0 + -12v Combine like terms: 12v + -12v = 0 -3u + 0 = 0 + -12v -3u = 0 + -12v Remove the zero: -3u = -12v Divide each side by '-3'. u = 4v Simplifying u = 4v
| .75(.25x+8)-(25x+2)=0.375(4-x)-.25x | | X/19=5/95 | | -6y-12=-18y-23 | | 6x-12=x-22 | | y-2=3(x+1) | | 15/45=x/12 | | x^2-20x-98=0 | | 9b+4=2b+46 | | 25r^3-16r=0 | | 25r^3-16r=0 | | 11-8x=7x+17 | | 139-5x=3x-19 | | 2(x+6)=3(x-4)+5 | | q-7/4=3 | | v/11=5/3 | | -42-2x=6-6x | | 7-9x=7x+18 | | (7x^3+4x)(x^2+2)= | | 4(x-3)=23-x | | 9(2+x)=63 | | 4x+13=94 | | 2(3-5+7)+6= | | 5(14-x)=60 | | 8(x+1)=48 | | 3x(3+5)=24 | | -32=4(x+3) | | (2x+4y)+(4x+7y)=180 | | -3x^2+21x=15 | | 5x+5+4x+5+35=180 | | 1=-.5(3k-4) | | 3.50x=84 | | (3+3.50)x=84 |